Role play in ethnographic production among the ludar “gypsies” of Mexico - Alvarado Solís, Neyra (Instituto de Altos Estudios Sociales, 2021)
The role play refers to the constant role shifts in the routines of circus, theater, and variety shows, which the ludar “gypsies” of Mexico perform in their tours across the northern part of the country. Role play evokes the anthropologist’s system of placesin fieldwork (Favret-Saada, 1977). In this system of roles, the anthropologist takes the role or roles assigned to her, or that she negotiates, which she reflexively takes on during fieldwork. The methodology and epistemology that underlie ethnography and anthropology are directly linked to the relationship between the researcher and the individuals with whom she conducts fieldwork, as well as the individuals and institutions of their surroundings. The dynamic relationships between ludars and non-ludars, places ludars, through the family performance, as those who “make someone do”, a dimension at the center of the social relations assigned to this population. The complexity of roles and relationships goes beyond this domain. The purpose of this text is to identify and explain the different roles within ludar life from the point of view of anthropology.